In-Hospital Opioid Consumption After the Previous Cesarean Delivery Weakly Predicts Opioid Consumption After Index Delivery: A Retrospective Cohort Study. Issue 4 (21st December 2022) - Komatsu, R.; Nash, M.; Mandalia, S.; Dinges, E.; Kamal, U.; Singh, D.; El-Omrani, H.; Anwar, A.; Delgado, C.; Ziga, T.M.; Carvalho, B.
Abstract : ( Anesth Analg . 2022;134:1280–1287. doi: 10.1213/ANE.0000000000005918) Opioid administration is a common form of analgesia for breakthrough pain following cesarean deliveries (CDs) when nonopioid medication is not sufficient. Pain severity can differ from patient to patient, so an individualized approach to care can be taken. Predicting in-hospital opioid consumption following a repeat CD has not been previously studied. The primary aim is to identify if prior opioid consumption 48 hours postoperatively following CD correlates with patient opioid consumption following index CD. The primary aim of the investigations was that an associated prediction would exist. Secondary aims included whether pain scores correlated and if obstetric and demographic variable improved prediction accuracy.